Translation as a Variety of Cross-Cultural Communication - Tomash Vrabel; Vrábely Tamás; Врабель Томаш (ORT Publishing, 2019)
Abstract. This paper is devoted to the analysis of translation both as a means and as a variety of cross-language and cross-cultural communication. Translation is regarded as a means of communication between representatives of different cultures and languages. Furthermore, translation is a process of cross-cultural interaction of speakers, a process of explaining one cultural code through another one.
Keywords: translation; cross-cultural communication; communicative theory of translation; linguoculture